The Influence of Principal Transformational Leadership and Work Climate on Primary School Teacher Performance - Nurbaeti; Nugraha Suharto; Asep Suryana (Journal of Innovation and Research in Primary Education, 2026)
This study aims to analyze the influence of transformational leadership of school principals and work climate on the performance of elementary school teachers in Plered District, Purwakarta Regency. The transformational leadership of the principal is considered the main factor that can create an inspiring and supportive work environment, while a conducive work climate plays a role in increasing the motivation and productivity of teachers in carrying out their duties. This study uses a quantitative approach with a correlational survey method to analyze the relationship between the principal's transformational leadership, work climate, and teacher performance. The research was carried out in an elementary school in Plered District, Purwakarta Regency with a population of 273 teachers. The sample of 152 respondents was determined through proportional random sampling. The research variables included transformational leadership, work climate, and teacher performance. Data was collected using a Likert scale questionnaire that has been tested for validity and reliability. Data analysis was carried out through descriptive statistics, prerequisite tests, correlations, determination coefficients, hypothesis tests with ANOVA, and linear regression using SPSS. The descriptive results showed that the teacher's performance was in the Good category with a general tendency of strong professionalism. Transformational leadership is also in the Good category with strength in inspirational motivation, while the work climate is considered conducive and stable. In terms of influence, transformational leadership contributes significantly to teacher performance by 82.3%, the work climate affects 77.3%, and transformational leadership affects the work climate by 74.1%. Simultaneously, transformational leadership and work climate explain 86.1% of teacher performance variations. The implications of the study confirm the importance of strengthening visionary leadership, collaborative culture, and teacher participation in decision-making. Suggestions are given to the education office, supervisors, principals, teachers, academics, and researchers to develop coaching programs, reflective supervision, as well as improve professionalism and collaboration based on the needs of elementary schools on a sustainable basis.